Pengendalian Kualitas Menggunakan Statistical Quality Control: Studi Kasus pada Proses Produksi Sepatu di PT. ABC - Burhan, Gilang Fatikhul; Frannita, Eka Legya (Fakultas Teknik Universitas Tulang Bawang, 2026)
The quality of footwear products such as shoes is a major factor that influences the success of a company in producing footwear products. Shoe companies usually have various quality control methods to maintain the production process. One of the most widely used methods in the industry is the statistical quality control method. PT ABC is a company that produces sports shoes located in Bandung. ABC Company is experiencing problems in terms of production, namely the number of defective products produced is still high. This study aims to apply statistical quality control to control the number of defects that appear in the production process. The application process is focused on the problems that arise in the screen printing division where there are many defects that appear during the production process. The steps taken in this study include data preparation and initial analysis using check sheets and Pareto diagrams, data adequacy tests, making p control charts, and analyzing results. Based on the control chart that has been made on the initial defect proportion and the proportion of defective data after improvements have been made to the screen printing process, it can be concluded that there is a decrease in the average value of the defect proportion of 0.02. This figure is quite significant. In addition, there was a drastic decrease in the LCL (lower control limit) value. This significant decrease is a positive indication that the improvements made to the screen printing process have succeeded in reducing product defects significantly. Keywords: Control Chart, Quality Control, Shoes Defect, Statistical Quality Control